Capacity Building for Farmers Through Focus Group Discussions (FGD) on Cattle Management in Baruga Village, Baruga Subdistrict: Peningkatan Kapasitas Peternak Melalui Focus Group Discussion (FGD) Manajemen Pemeliharaan Sapi Di Kelurahan Baruga, Kecamatan Baruga - Nafiu, La Ode; Pagala, Muh. Amrullah; Malesi, La; Auza, Fuji Astuty; Aka, Rahim; Badaruddin, Rusli; Napirah, Astriana (Politeknik Negeri Fakfak, 2025)
The community service activity was carried out in Baruga District, specifically in Baruga Village, Kendari City, with the aim of improving the capacity of beef cattle farmers in sustainable livestock management. The main problems faced by farmers in this area include a lack of technical knowledge about feeding, barn sanitation, and livestock health management. The approach used in this activity was a Focus Group Discussion (FGD) and participatory field observation. The activities in this community service consisted of three stages, namely preparation, implementation, and evaluation. The preparation stage included field surveys and identification of farmers' needs, while the implementation stage was carried out through FGDs to explore actual problems and formulate joint solutions, as well as direct observation at the barn location. The evaluation was carried out by collecting participant feedback and documenting the results of the activities for further program improvement. The results of the activities show that the FGD method is effective in establishing two-way communication between resource persons and farmers, as well as encouraging active participation in identifying and solving problems. Farmers gained a better understanding of the importance of feed management, health, and livestock waste management. In addition, several follow-up plans were produced, such as training in planting forage crops for livestock, making ammoniated straw, and processing compost from livestock waste. These activities not only strengthened the technical capacity of farmers, but also raised awareness of the importance of integrated and environmentally friendly livestock management.